Implementasi Pembiayaan Muḍārabah pada Bank Syariah di Indonesia: Kajian Rukun, Syarat, dan Manfaatnya - Nisa Afifah; Mohammad Fajar At Toriq; Nailatul Muhajiroh; Ariij Salsabil Alamsyah; Fahmi Makraja (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
This study examines the implementation of muḍārabah financing in Indonesian Islamic banks by analyzing its pillars, legal requirements, operational mechanisms, and its economic, social, and Sharia-related benefits. The research is motivated by the growing demand for interest-free financing in Indonesia, particularly among micro, small, and medium enterprises (MSMEs) that dominate the national economic structure yet face limited access to conventional capital systems. A qualitative library research method was employed, drawing on fiqh mu’āmalah literature, DSN-MUI fatwas, Islamic banking regulations, and financial institution reports. The analysis combines descriptive and normative approaches to assess the compatibility of muḍārabah principles with contemporary banking practices. The findings indicate that the pillars and conditions of muḍārabah comprising contracting parties, capital and business objects, and contractual agreement have been systematically applied by Islamic banks such as BSI, BRI Syariah, and BNI Syariah. Implementation includes assessment of feasibility, determination of profit-sharing ratios, continuous monitoring, and periodic evaluation. Muḍārabah significantly contributes to MSME empowerment, business expansion, and poverty reduction through equitable profit-sharing mechanisms. Socially, muḍārabah fosters cooperative relationships, transparency, and ethical business conduct. From the perspective of maqāṣid sharia, it aligns with the objectives of preserving wealth (ḥifẓ al-māl), protecting religious values (ḥifẓ al-dīn), and preventing society from falling into exploitative interest-based transactions. In conclusion, muḍārabah financing plays a strategic role within Islamic finance as an instrument that not only upholds Sharia principles but also produces substantial benefits for community welfare and real-sector development.